Evaluasi Kebijakan Penganggaran Berbasis Kinerja pada Daftar Isian Pelaksanaan Anggaran Satuan Kerja Kantor Pusat Direktorat Jenderal Perbendaharaan di Jakarta - Akhlis Febriyanto; Muhammad As’Ad (Institut Ilmu Sosial dan Manajemen Stiami, 2025)
Performance-Based Budgeting is an approach that connects budget allocation with output and outcome. It is expected that Performance-Based Budgeting can help improve the quality of budget preparation by identifying outputs and outcomes, followed by identifying the necessary inputs to produce those outputs and outcomes. The Central Office of the Directorate General of Treasury has a complex organizational and budgetary structure and is the largest Work Unit within the Directorate General of Treasury. It has implemented the Performance-Based Budgeting policy in its annual budget preparation. This research aims to analyze and evaluate the Performance-Based Budgeting policy at the Central Office of the Directorate General of Treasury, analyze the factors hindering the policy, and provide recommendations on measures that can be taken to address the obstacles in the policy’s implementation. This research uses a qualitative method, collecting data through in-depth interviews with key stakeholders, field observations, and documentation studies. The evaluation is conducted using criteria developed by William N. Dunn (2021:610), covering effectiveness, efficiency, adequacy, equity, responsiveness, and policy precision. The results of the research show that the performance-based budgeting policy has met the criteria of effectiveness, efficiency, adequacy, equity, and policy precision, but has not met the responsiveness criterion. In general, this policy has made a positive contribution to budget planning and preparation, but there are still obstacles that need to be addressed. The proposed recommendations include the establishment of a special team, the development of a resource forum, continuous training, and improved synchronization of planning and budgeting data.